Scales and hierarchies : a cross-disciplinary perspective - Bornkessel-Schlesewsky, Ina, 1979-; Malʹchukov, A. L. (Andreĭ Lʹvovich); Richards, Marc (Trends in linguistics. Studies and monographs ;, 2015)
The volume advances our understanding of the role of scales and hierarchies across the linguistic sciences. Although scales and hierarchies are widely assumed to play a role in the modelling of linguistic phenomena, their status remains controversial, and it is these controversies that the present volume tackles head-on.